2019
DOI: 10.1097/md.0000000000016291
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of inflammatory bowel disease in Mexico from a nationwide cohort study in a period of 15 years (2000–2017)

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 49 publications
2
35
1
9
Order By: Relevance
“… 29 In a nationwide study performed between 2000 and 2017, the highest incidence of UC was reported in 2015 (0.16/100,000 person-years) compared with previous years, the number of UC diagnoses increased by an average of 10.8 ± 6.3% per year, and the incidence of new UC cases increased 5.3-fold from 2000 to 2016. 27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 In a nationwide study performed between 2000 and 2017, the highest incidence of UC was reported in 2015 (0.16/100,000 person-years) compared with previous years, the number of UC diagnoses increased by an average of 10.8 ± 6.3% per year, and the incidence of new UC cases increased 5.3-fold from 2000 to 2016. 27 …”
Section: Resultsmentioning
confidence: 99%
“…18,29,36 Extraintestinal manifestations A total of 14 studies reported the presence of extraintestinal manifestations (EIMs) in patients with UC (Table 4), with the proportion of patients with UC who experienced EIMs ranging from approximately 26% in Mexico and Puerto Rico to 89.4% in Sergipe, Brazil. 18,27,33 The most prevalent EIMs that were reported were arthropathies/ arthritis, articular EIMs and abnormal bone mineral density.…”
Section: Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Хронічні запальні захворювання кишок (ХЗЗК) залишаються однією з найвагоміших проблем гастроентерології і становлять близько 10,0 % всієї хронічної патології органів травлення [1]. Неспецифічний виразковий коліт (НВК) є одним із найтяжчих захворювань не тільки кишечника, але й органів травлення [2], що привертає увагу як лікарів, так і науковців у всьому світі. Це обумовлено тим, що майже 1 млн осіб у США та понад 2 млн осіб в Європі страждають від ХЗЗК [3].…”
Section: вступunclassified
“…Over the last years, a decrease in the incidence of gastric cancer and peptic ulcer disease and a simultaneous rise in the incidence of inflammatory bowel disease (IBD) have been reported [3][4][5][6]. A study carried in Hungary with 133 patients with IBD and a similar control number found a significant inverse relationship with HP infection.…”
Section: Introductionmentioning
confidence: 99%